Optimasi Parameter 3D Printing pada Material PETG terhadap Kekuatan Tarik dan Building Time Menggunakan Metode Taguchi Grey Relational Analysis - Achmad Faizal Cholis; Bayu Wiro Kurniawan; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Nowadays 3D printing technology is often used as a production machine, but production efficiency and good mechanical properties are priorities in the production process. Tensile strength and production time (building time) are some of the response variables of mechanical properties and production efficiency. In this study, the 3D printing parameters like nozzle size, layer height, print speed, and infill pattern will be used as an independent variables to obtain optimal output for tensile strength response and building time. The experimental design was calculated using the Taguchi method with an orthogonal matrix ( ) with 3 replications. Then the data was analyzed using Gray Relational Analysis to obtain the optimal combination of parameters for the combined response. After the prediction experiment had been conducted, a confirmation experiment was used as a validation of the experiment success. The optimal parameters obtained are nozzle size 0.8 mm, layer height 0.2 mm, print speed 50 mm/s, and concentric infill pattern with an average tensile strength of ±25.033 Mpa with a building time of ±28.0056 minutes. After analysis, the nozzle size parameter has a contribution of 44.39%, layer height of 42.31%, print speed of 1.18%, and infill pattern of 12.13% to the combinedresponse.